Communication, Technology, and Coordination in Public Sector Crisis Response - Arafat; Rahayu, Triwik Puji (Indonesian Scientific Publication, 2024)
This narrative review examines strategies, policies, and lessons learned in crisis management within public administration, focusing on institutional resilience, governance structures, communication, cyber resilience, and technology integration. The purpose of this review is to synthesize current evidence and identify the main factors influencing effective crisis responses. A systematic search of peer-reviewed literature was conducted using databases including Scopus, PubMed, and Google Scholar, employing keywords such as crisis management, public administration, emergency response, disaster management, resilience, and risk communication. Inclusion criteria emphasized studies addressing governance, policy, and institutional practices in crisis contexts, while irrelevant or non-peer-reviewed sources were excluded. Findings reveal that institutional resilience, supported by managerial capacity, emergency planning, and adaptive responses, is essential for sustaining services during crises. Governance structures that balance centralization and decentralization, coupled with strong coordination, are more effective than rigidly centralized or fragmented systems. Transparent communication fosters citizen trust, as demonstrated in Taiwan and Singapore, while communication failures, such as in Brazil, undermine compliance. Emerging evidence highlights the critical role of cyber resilience, with cyberattacks disrupting public services globally during COVID-19. The integration of advanced technologies, supported by administrative capacity, further enhances crisis responsiveness. However, disparities between developed and developing countries underscore the role of systemic inequalities in shaping outcomes. The review concludes that future policies should strengthen institutional capacity, promote participatory governance, and invest in digital resilience, while further research is needed on long-term and cross-context evaluations.